The oral tradition in Désert, by Le Clézio - Assunção, Islene França de (Lettres Françaises, 2013)
Désert reveals a constant of Le Clézio’s work: the city shows an evil character that opposes to the natural spaces, source of incomparable peace and liberty. Therefore, the desert is presented as a sacred space, favorable to the dream and the remembrance of past, what gives opportunity to the emergence of legends, beliefs and cultural traditions of a people. It is precisely in this space that arise the storytellers and the oral tradition of Désert. The storytellers’ narratives, this oral literature, are responsible for the preservation of legends and traditions of people which the stories narrate: the girl Lala and her ancestors, the blue men of desert.